(untitled) (Research Journal Tahqeeqat, 2025)
The term Pakistanism had emerged in literary circles soon after the establishment of Pakistan. In the novel "Rakh", the oppression and oppression of history have been described in the context of Pakistan, proving Pakistanism. The novel presents the social, political, economic and moral conditions of Pakistan over the past fifty years, and the crises that this country has gone through. From the partition of the subcontinent to the wars of 1965 and 1971 and the separation of East Pakistan, the country’s conditions, the politics of gaining power and the political and social struggles, in addition to the mental and emotional tragedies, anxiety, dissatisfaction and insecurity that arose as a result of these conditions and events. The fall of Dhaka and its effects on the Pakistani nation have been shown in the national context. Mustansar Hussain Tarar also raises his voice against oppression and violence in this novel. He not only protests against the oppression of a nation, but he also wants to end prejudice and hatred. His view is that the people of a nationality and state should live together in unity.